2021
DOI: 10.1021/acssuschemeng.1c04030
|View full text |Cite
|
Sign up to set email alerts
|

Green Semisynthetic Cascade to Ligstroside, Ligstroside Aglycone, and Oleocanthal

Abstract: Ligstroside, ligstroside aglycone, and oleocanthal are extra virgin olive oil (EVOO) bioactive phenols poorly represented in olive leaves. Semisynthetic pathways to achieve them, starting with largely available natural precursors, are proposed as alternative solution with respect to their low effective extraction or total synthesis. In the present work, we propose the first green chemocatalytic method to obtain, in the same semisynthetic cascade, ligstroside, ligstroside aglycone, and oleocanthal starting from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…8 a). Compared to the previously reported method using microwave-assisted Krapcho dealkoxycarbonylation, this catalytic reaction can produce oleocanthal in relatively better yield from ligstroside 27 .
Figure 8 Catalyst applications.
…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…8 a). Compared to the previously reported method using microwave-assisted Krapcho dealkoxycarbonylation, this catalytic reaction can produce oleocanthal in relatively better yield from ligstroside 27 .
Figure 8 Catalyst applications.
…”
Section: Resultsmentioning
confidence: 90%
“…Smith et al reported the total synthesis of oleacein from d -lyxose over 10 steps, with a total yield of 13% 25 . Compared to total synthesis, semi-synthesis is a more efficient, more economical, and greener alternative 26 , 27 . Vougogiannopoulou et al reported the direct conversion of oleuropein into oleacein via Krapcho decarboxylation using two equivalents of sodium chloride; however, the oleacein yield was only 20% 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Mancuso and co-workers 42 proposed a green catalytic method to obtain ligstroside 3, ligstroside aglycone 5 and oleocanthal 7 starting from oleuropein 4, in the same semisynthetic cascade. Based on Samara's strategy, 39 the authors started from oleuropein 4.…”
Section: Ligstrosidementioning
confidence: 99%
“…More recently, the synthesis of oleocanthal 7 was described by Mancuso et al 42 starting from oleuropein 4 (Scheme 8), in four steps with 13% overall yield. The desired compound was obtained by the MW-assisted Krapcho dealkoxycarbonylation, from ligstroside 3.…”
Section: Oleocanthalmentioning
confidence: 99%
See 1 more Smart Citation